122 A Medication Self-Management Intervention to Improve Medication Adherence for Older People with Multimorbidity: A Pilot Trial. (16th March 2021) - Yang, C; Hui, Z; Zhu, S; Wang, X; Tang, G; Lee, D T F
Abstract: Introduction: Medication self-management support has been recognised as an essential element in primary health care to promote medication adherence and health outcomes for older people with chronic conditions. A patient-centred intervention empowering patients and supporting medication self-management activities could benefit older people. This pilot study tested a newly developed medication self-management intervention for improving medication adherence among older people with multimorbidity. Method: This was a two-arm randomised controlled trial. Older people with multimorbidity were recruited from a community healthcare centre in Changsha, China. Participants were randomly allocated to either a control group receiving usual care (n = 14), or to an intervention group receiving three face-to-face medication self-management sessions and two follow-up phone calls over six weeks, targeting behavioural determinants of adherence from the Information-Motivation-Behavioural skills model (n = 14). Feasibility was assessed through recruitment and retention rates, outcome measures collection, and intervention implementation. Follow-up data were measured at six weeks after baseline using patient-reported outcomes including medication adherence, medication self-management capabilities, treatment experiences, and quality of life. Preliminary effectiveness of the intervention was explored using generalised estimating equations. Results: Of the 72 approached participants, 28 (38.89%) were eligible for study participation. In the intervention group, 13 participants (92.86%) completed follow-up and 10 (71.42%) completed all intervention sessions. Ten participants (71.42%) in the control group completed follow-up. The intervention was found to be acceptable by participants and the intervention nurse. Comparing with the control group, participants in the intervention group showed significant improvements in medication adherence (β = 0.26, 95%CI 0.12, 0.40, P < 0.001), medication knowledge (β = 4.43, 95%CI 1.11, 7.75, P = 0.009), and perceived necessity of medications (β = −2.84, 95%CI -5.67, −0.01, P = 0.049) at follow-up. Conclusions: The nurse-led medication self-management intervention is feasible and acceptable among older people with multimorbidity. Preliminary results showed that the intervention may improve patients' medication knowledge and beliefs and thus lead to improved adherence.